(untitled) (Revista de Medicina Clinica, 2019)
Background: Chronic rhinosinusitis with polyps is a disease with high prevalence, it is estimated that it affects 2-5% of the general population. Frequently in association with pulmonary pathologies (bronchial asthma with a prevalence of 6.7%, sensitivity to aspirin, Samter’s triad, cystic fibrosis). Materials and Methods: Cohort study of patients with the diagnosis of chronic rhinosinusitis with nasal polyps and concomitant asthma, both genders, age â‰¥18, who had indication and surgical programming, spirometry, SNOT quality of life questionnaire. A uni-bivariate statistical analysis was performed to know the behavior of these variables, with 95% confidence intervals (CI), a p-value equal to or less than 0.05 was considered statistically significant. Results: The average age of the patients studied was 46 years, 10 (50%) female patients and 10 (50%) male patients, the SNOT-22 questionnaire prior to surgery reveals an average of 36 Â± 18 points (p = 0.0001), while the average after surgery was 6.0 Â± 6.0 (p = 0.0001). The lung volumes pre-surgical of 76 Â± 10, and postoperative of 80 Â± 4 (p = 0.0001) showed a significant improvement of lung function in relation to pulmonary obstruction.